PENGARUH NILAI TUKAR RUPIAH, INFLASI DAN THE FED TERHADAP INDEKS HARGA SAHAM GABUNGAN DI BURSA EFEK INDONESIA PERIODE 2014-2018 - Andi Indrawati3, Bellinus Chandra Feta1 Robin Jonathan2 (EKONOMIA, 2021)
The purpose of this study is to find out how the influence of independent and dependent variable simultaneously and partially.The analytical tool used in this research is Descriptive Statistics Analysis, Classical Assumptions Test which includes: Normality Test, Linearity Test, Multicollinearity Test, Autocorrelation Test, Heteroscedasticity Test, Multiple Linear Regression Analysis, and Goodness of Fit.The results of the study are: 1) Exchange Rate has a negative and partially significant effect on the CSPI. 2) Inflation has a negative and not significant effect partially on the CSPI. 3) The Fed has a positive and partially significant effect on the CSPI. 4) Exchange Rate, Inflation and the Fed have a significant effect on the CSPI.The conclusions of this research hypothesis are: 1) Exchange Rate has a negative and significant influence partially on CSPI on the Indonesia Stock Exchange (BEI) in the 2014-2018. This means that changes in the Rupiah Exchange Rate have a significant negative effect on CSPI. 2) The results of this study indicate that the inflation has a positive and not significant effect partially on CSPI on the Indonesia Stock Exchange (BEI) in the 2014-2018. It means that inflation fluctuation do not have a significant negative effect on CSPIÂ  3) The results of this study indicate that the Fed has a positive and partially significant effect on CSPI on the Indonesia Stock Exchange (BEI) in the 2014-2018. The Fed fluctuation has a significant positive effect on CSPI. 4). The results of this study indicate that Exchange Rate, Inflation and the Fed simultaneously have a significant positive effect on CSPI on the Indonesia Stock Exchange in the 2014-2018.